The relationship between perfectionism and phishing susceptibility - Chan, Krystal Jiayi (Nanyang Technological University, 2024)
The present study sought to explore the influence of perfectionism on phishing from the perspective of the heuristic-systematic model (HSM) of information processing. HSM is a framework underlying successful phishing attacks, which can be influenced by perfectionism. The current study’s design was a 2x4 repeated-measures, mixed between and within-subjects design. A target of 150 responses was specified for the study. However, only 73 responses were valid. Participants (n = 73) completed a self-report questionnaire measuring their levels of trait perfectionism and perfectionistic self-presentation, before viewing a series of emails. After viewing each email, they self-reported their likelihood of clicking on the embedded links (i.e., phishing susceptibility) and confidence in their judgement. Repeated-measures ANOVA was conducted to analyse the data. The results showed a positive relationship between trait perfectionism and phishing susceptibility (r = .250, p < .05), with a small effect size. Furthermore, a positive relationship was demonstrated between perfectionistic self-presentation (r = .338, p < .01), with a medium effect size. No moderating effects were observed for both trait perfectionism and perfectionistic self-presentation; on the relationship between the use of persuasion principles in phishing emails and phishing susceptibility. The results suggested that both trait perfectionism and perfectionistic self-presentation could be antecedents of phishing susceptibility.